The Financial Feasibility Analysis Of Organic Waste Processing Business At The Central Market (Case Study: Kemang Market (Tu) Bogor City) - Pratama, Ihsan; Aminah, Mimin; Refipal Sembiring, Indra; Firmansyah, Irman (Cita Konsultindo Research Center, 2024)
Waste management poses a significant challenge in addressing the waste problem. PT BTS introduces SWASPRO (Smart Waste Processing) program, offering innovative solutions to waste management aimed at reducing the amount of waste sent to landfills. This study aims to determine whether SWASPRO is an optimal alternative for waste management, assess its financial feasibility, and evaluate the sustainability status and policy directions of waste management. Data in this study will be analyzed using the Google Worksheet Financial Feasibility Analysis and Sustainability Analysis with the help of EXsimpro software through the Multiaspect Sustainability Analysis (MSA) technique. The results show that SWASPRO is a viable program to implement.